The Existence of The Local Public Broadcasting Institution Radio Irama FM In The Midst of Digital Transformation In Public Information Dissemination - Wirawan, Riska; Laksito, FX (Indonesian Journal Publisher, 2025)
The aim of the research is to describe and analyze the existence of the local public broadcasting institution Radio Irama Fm in the midst of digital transformation in the distribution of public information. The type of research used in this research is descriptive qualitative. The data used are primary data and secondary data. Data collection techniques using interviews, observation, and documentation. The technique used in this research is inductive using phenomenological procedures (Moleong, 2014). Based on the results of the study it can be concluded that 1) indicators of organizational goals have been determined at the local public broadcasting institution Irama Fm radio, to achieve existence in the midst of a rapidly growing digitalization stream; 2) this leadership is a character possessed by each leader which will have a direct impact on the existence and progress of an organization. The pattern of relationship between superiors and subordinates will affect harmonization and create a sense of kinship in an organization. 3) at LPPL Radio Irama Fm there is a clear organizational structure for the division of labor, although in some time there has been a change in leadership. This is an innovative effort to maintain the existence of LPPL Radio Irama Fm amidst the current digital transformation. 4) The responsibility has been firmly held by all employees at LPPL Radio Irama Fm to maintain existence in the midst of the digitalization era, even though there are still obstacles that arise in the field